Antihypertensive medication use during pregnancy in a real-world cohort of patients diagnosed with a hypertensive disorder of pregnancy - Garcia, Julian E.; Mulrenin, Ian R.; Nguyen, Anh B.; Loop, Matthew S.; Daubert, Melissa A.; Urrutia, Rachel; Lee, Craig R. (Frontiers in Cardiovascular Medicine, 2023)
Hypertensive disorders of pregnancy (HDP) are rising in prevalence and associated with adverse maternal and infant health outcomes. Current guidelines recommend labetalol, nifedipine, and methyldopa as acceptable first-line agents to treat HDP in outpatient settings. However, the current practice regarding antihypertensive medication usage and selection remain unclear. A retrospective, observational cohort study was conducted in 1,641 patients with a physician diagnosis of HDP who delivered at two academic medical centers in North Carolina from 2014-2017. Use of any antihypertensive medication, and the agent selected, at any encounter during pregnancy or on the delivery date was collected from the electronic health record. Proportions were compared across HDP diagnosis (eclampsia/severe preeclampsia, chronic hypertension with superimposed preeclampsia, preeclampsia, gestational hypertension) by Chi-square tests and multivariable logistic regression. Antihypertensive medications were used in 1,276 (77.8%) patients overall. Among treated patients, labetalol (74.9%) was the most frequently used medication followed by nifedipine (29.6%) and hydralazine (20.5%). Methyldopa was used infrequently (4.4%). HDP type was the strongest factor associated with use of an antihypertensive agent. Relative to gestational hypertension, antihypertensive use was significantly more likely (odds ratio [95% CI]) in patients with severe preeclampsia (5.94 [3.85-9.16]), chronic hypertension with superimposed preeclampsia (4.99 [3.46-7.19]), and preeclampsia (2.13 [1.61-2.82]). In a real-world setting, antihypertensive medication use among HDP patients was common, labetalol, nifedipine, and hydralazine were the most commonly selected agents, and increasing HDP severity was associated with a higher likelihood of antihypertensive use. Future studies comparing medication effectiveness in pregnant patients with distinct HDP diagnoses are needed.